Greenland, Jaette Glacier at Fraenkel Land, now Northeast Greenland National Park - Boyd, Louise Arner, 1887-1972 (1931)
Fig 151 - Jaette Glacier at head of Ice Fiord. The sharp peak (1835 meters) is on the north side of Fraenkel Land. Aug. 4, 1931. (X). (Caption from Boyd, L. A. (1935). The Fiord Region of East Greenland (pp. 112). New York: American Geographical Society.) Jaette Glacier at head of Ice Fiord. The sharp peak (1835 meters) is on the north side of Fraenkel Land. Aug. 4, 1931. See Fiord Region of East Greenland, Fig. 151. Boyd, Louise A. (1935). The Fiord Region of East Greenland. New York: American Geographical Society